Nonparaxial Coefficients Influence of High Intense Laser Beam on The Relativistic Self-Focusing Inside Plasma - Fatima Dhari Jabbar; Çiğdem Yüksektepe Ataol; Ibtisam Jaafer Abd-Ali; Munther B. Hassan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
In this article, the influence of the nonparaxial deformation coefficients of laser beam wavefront on the self-focusing phenomenon has been investigated. Due to the relativistic nonlinear interaction between the nonparaxial laser beam and plasma, a self-focused laser beam will have appeared. Appropriate differential equations related to laser beam behavior inside plasma have been derived and then is solved numerically by designing a suitable Matlab program. The result shows that the self-focusing of the laser beam is increasing with decreeing of both the nonparaxial deformation coefficients but the second-order spherical deformation coefficient is greater compared with the spherical deformation coefficient of the fourth order. This study also investigates the influence of the laser beam intensity, plasma frequency, and laser beam diameter on the laser beam self-focusing inside plasma at high enough magnitudes of the laser beam intensity, plasma frequency and laser beam diameter, a high self-focusing of the laser beam will appear. In contrast, the laser beam defocusing phenomenon will be dominant at low magnitudes.